ENHANCING THE POTENTIAL ECOTOURISM OF ANCIENT VOLCANO NGLANGGERAN IN THE DEVELOPMENT OF TOURIST DESTINATION AT GUNUNGKIDUL YOGYAKARTA SPECIAL REGENCY - Isdarmanto Isdarmanto; Dyah Wahyuning Tyas; Nur Huswatun Khasanah (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
In observation of this study the authors are interested in aspects Ecotourism the Ancient Volcano of Nglanggeran, which has the potential of uniqueness nature, mysterious and beautiful landscape as well as regional partner of reservoir Nglanggeran that has appeal. Those interesting places were located at Pathuk Wonosari Gunung kidul in Yogyakarta Special Regency. When the sun set come the panorama were really beautiful and amazing views. Since 2011-up to now that places were not seriously managed by participation from the stakeholder of government and private investor, and being handled by the local community management. In some conditions facilities and security aspects was not well accomodated, for there is no safe guard or guides at the location, only by exception or upon customer request. The ancient volcano sights and Embung Nglanggeran ponds were a pair of specific attractions that have to be developed better. Mostly tourist after enjoy the panorama and hiking track to the top of ancient volcano Nglanggeran, they went to see Embung Nglanggeran ponds. Awfully there is no public transportation, and the visitors have to go by their own transportation. More over the road were badly and dangerous. The local communities and government as stakeholder have to support the area of Nglanggeran district to be more seriously, as well as the collaboration of local community and government being well organized.Keywords: Ecotourism; the Ancient Volcano of Nglanggeran